EXPLORING UNDERSTANDING OF PADDY ZAKAT AMONG FARMERS IN SABAK BERNAM, SELANGOR - Nur Fariza Yacob,; Mohd Ariff Mohd Daud, (Journal of Islamic, Social, Economics and Development, 2022)
Paddy cultivation is among the major agricultural sectors in Malaysia. As paddy iscommercially produced, it is subjected to zakat, an obligation for the producer to donate certainproportion of wealth. A form of worship, zakat also contributes towards the economicdevelopment of Muslims in Malaysia. With this background, this study focuses on exploring theunderstanding of paddy zakat among farmers in Sabak Bernam, one of the biggest riceproducing areas in Malaysia. This study uses qualitative method in which farmers who cultivatepaddy in this district will be interviewed to gauge their level of understanding of paddy zakat.In addition, this study also intends to explore views of the farmers regarding zakat institutionand how to improve management of paddy zakat collection. The research is expected to gaugethe level of understanding of paddy zakat among the farmers in Sabak Bernam and recommendimprovements for zakat institution in Selangor in managing paddy zakat collection.